Altered Subcellular Localization of a Tobacco Membrane Raft-Associated Remorin Protein by Tobamovirus Infection and Transient Expression of Viral Replication and Movement Proteins - Sasaki, Nobumitsu; Takashima, Eita; Nyunoya, Hiroshi (Frontiers in Plant Science, 2018)
Remorins are plant specific proteins found in plasma membrane microdomains (termed lipid or membrane rafts) and plasmodesmata. A potato remorin is reported to be involved in regulating negatively potexvirus movement and plasmodesmal permeability. In this study, we isolated cDNAs of tobacco remorins (NtREMs) and examined roles of an NtREM in infection by tomato mosaic virus (ToMV). Subcellular localization analysis by using fluorescently tagged NtREM, ToMV, and viral replication and movement proteins indicated that virus infection and transient expression of the viral proteins promoted the formation of NtREM aggregates by alteration of the subcellular distribution of NtREM, which was localized uniformly on the plasma membrane under normal conditions. NtREM aggregates were often observed to be associated closely with endoplasmic reticulum networks and also bodies of the 126K replication and movement proteins. The bimolecular fluorescence complementation assay indicated that NtREM might interact directly with the movement protein on the plasma membrane and around plasmodesmata. In addition, transient overexpression of NtREM facilitated ToMV cell-to-cell movement. Based on these results, we discuss possible roles of the tobacco remorin in tobamovirus movement.